Structural and optical characterization of Mg doped GaAs nanowires and the impact of the functionalization with Au nanoparticles - Jaló, Daniel Jorge Pires (2017)
GaAs, nanowires, nanotechnology, semiconductors, spectroscopy, photoluminescence, photoluminescence excitation, cathodoluminescence, Raman, nanoparticles, nanorods, functionalization, image charge effect.